KONSEP MANUSIA DALAM PENDIDIKAN HAKIKAT MANUSIA THE PERFECT MAN - Nur Hidayat; Fauzi (STKIP Subang, 2023)
ABSTRACT This study aims to determine the human concept in education, especially regarding human nature (The Perfect Man) by using the literacy method. The results are known as follows Humans who have been created by Allah SWT who have special features from birth have differences and various potentials. Humans have various features, therefore it has various terms such as superior humans, perfect humans, ideal humans, plenary humans, the perfect men, and perfect humans by means of holistic education. Holistic education focuses more on the process so that an individual gains needed knowledge that can be applied in his social environment. There are five important factors that continuously and simultaneously build human personality. These factors are as follows, First, the mother's factor which provides a spiritual structure and dimension which is full of love and tenderness, Second, the father's factor which provides a dimension of strength and self-esteem, Thirdly, the school factor which helps to form outward character, Fourthly, the community factor which provide an empirical environment, Fifth, the general cultural factors of society that provide a pattern of human life